Factors Affecting Human Resources Accounting and Its Impact on Profitability and Performance Improvement: Applied Study in General Company for Engineering Industries - Ban Abdul-Kadhm Abdulaali; Alyaa Hussein Mohmmed Ali Alesaa; Hala AbdulAmeer Dhahir (International Journal of Economics, Management and Accounting, 2025)
The research aims to identify the factors affecting human resources accounting and their impact on profitability and performance improvement, as there is still limited evidence regarding the factors that play a role in determining the level of disclosure of information related to human resources in the financial reports of these banks, as well as providing an indicator to measure the level of disclosure of human resources, which enables bank departments to assess the level of this disclosure in their reports mechanism. The research was applied in your State Company for Engineering Industries, a public company affiliated with the Iraqi Ministry of Industry, and the research was applied for the period (2021-2024). The study came to a number of conclusions, chief among them that business organizations' financial reports do not disclose human resources, which means that these reports do not contain a significant portion of the information that would aid the various groups of users in making informed decisions about these organizations.  Given the growing significance of innovation, creativity, and the intensity of competition in today's world, modern organizations are depending more and more on human resources to accomplish their objectives and obtain a competitive edge. This calls for the provision of pertinent information.